THE EFFECT OF HEALTH, EDUCATION, INFRASTRUCTURE AND ECONOMIC GROWTH EXPENDITURES ON THE HUMAN DEVELOPMENT INDEX IN ACEH PROVINCE - Ramziati Piqqa; Devi Andriyani; Ratna Husein (LPPM Universitas Malikussaleh, 2022)
The influence of expenditure on health, education, infrastructure, and economic growth on the Human Development Index in Aceh province was investigated in this study. The panel data regression approach was utilized to investigate the connection between the independent and dependent variables. The panel data model was chosen using the Chow, Hausmant, and LM-Tests. The Random Effect Model was found most effective. The findings indicated that government expenditure on health, education, and infrastructure positively and significantly affected the Aceh Province Human Development Index, however economic development had no effect on the Aceh Province Human Development Index. Simultaneously, government expenditure on health, education, infrastructure, and economic growth affected the Aceh Province Human Development Index favorably and considerably. The magnitude of the effect was 0.7528, or 75.28 percent, with the remaining 24.22 percent influenced by factors outside the model.